1999
DOI: 10.1007/s004399900078
|View full text |Cite
|
Sign up to set email alerts
|

Cell fusion corrects the 4-nitroquinoline 1-oxide sensitivity of Werner syndrome fibroblast cell lines

Abstract: We have shown that Werner syndrome (WRN) fibroblast cell lines are unusually sensitive to the DNA-damaging agent 4-nitroquinoline 1-oxide (4NQO), though not to gamma radiation or to hydrogen peroxide. The fusion of 4NQO-sensitive WRN and 4NQO-resistant control fibroblast cell lines generated proliferating WRN x control cell hybrids that expressed WRN protein and were 4NQO-resistant. These results establish the recessive nature of 4NQO sensitivity in WRN cell lines and provide a cellular assay for WRN protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…g-induced regulation of common stress response genes was almost similar in old and WS cells (Figure 3a), which is in agreement with the observation that WS cells do not display significant g-irradiation hypersensitivity (Prince et al, 1999). g-Irradiation can affect all cellular components and induces several types of damage: AP sites, base modifications, DNA-DNA and DNAprotein crosslinks and strand breaks, with the most deleterious effect being DNA double-strand breaks.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…g-induced regulation of common stress response genes was almost similar in old and WS cells (Figure 3a), which is in agreement with the observation that WS cells do not display significant g-irradiation hypersensitivity (Prince et al, 1999). g-Irradiation can affect all cellular components and induces several types of damage: AP sites, base modifications, DNA-DNA and DNAprotein crosslinks and strand breaks, with the most deleterious effect being DNA double-strand breaks.…”
Section: Discussionsupporting
confidence: 87%
“…WS cells have a selective survival sensitivity to 4NQO which is intriguing, as they are not sensitive to UV or most other DNA-damaging agents (Ogburn et al, 1997;Prince et al, 1999). The mechanism underlying the 4NQO sensitivity of WS cell lines is not known.…”
Section: Discussionmentioning
confidence: 99%
“…We used complementary colony‐size distribution (CSD; Smith et al ., 1978), colony‐forming efficiency (CFE) and proliferative survival (Poot et al ., 2002b) assays to analyze the survival and proliferation of primary and SV40‐transformed fibroblasts that had been mutation typed and shown to lack WRN protein (Prince et al ., 1999; Moser et al ., 2000; Huang et al ., 2006; additional results not shown). Primary WS fibroblasts showed a marked reduction in median colony cell number in CSD assays as well as a reduced CFE in the absence of exogenous DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of chromosomal translocations, deletions and re-arrangements in primary WS fibroblast and lymphocyte cultures led to the suggestion that WS was a chromosomal instability syndrome (Hoehn et al ., 1975;Salk et al ., 1985), and that the cellular phenotype of WS might be an expression of constitutive genomic instability. Subsequent analyses revealed that the chromosomal instability of WS cells could be accentuated by DNA damage (Gebhart et al ., 1988), and that WRN-deficient cells were selectively sensitive to killing by 4-nitroquinoline 1-oxide (4-NQO ;Gebhart et al ., 1985;Ogburn et al ., 1997;Prince et al ., 1999;Hisama et al ., 2000); by camptothecin, a DNA topoisomerase I inhibitor (Okada et al ., 1998;Poot et al ., 1999); and most notably and strongly by DNA cross linking drugs such as cis -platinum ( cis -Pt), mitomycin-C, or 8-methoxypsoralen + UV light (8-MOP+UV; Poot et al ., 2001Poot et al ., , 2002a.…”
Section: Introductionmentioning
confidence: 99%
“…WRN Multimerization Domain Disrupts WRN Function in Vivo-Cells lacking functional WRN protein have a markedly increased sensitivity to the DNA-damaging drugs camptothecin and 4-nitroquinoline 1-oxide (33)(34)(35)(36)(37). To determine the influence of WRN(250 -366) expression on WRN function, we carried out toxicity assays using cells expressing FLAG-WRN(250 -366).…”
Section: Identification Of Wrn Exonuclease Domain Boundaries Andmentioning
confidence: 99%